PRAGMALINGUISTIC AND LINGUOPOIETIC ANALYSIS OF IRONY - A.A.Hasanov (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
In the article, research was conducted on the importance of the irony tool in the language of the artistic work, increasing its aesthetic value. The essence of irony is approached from a pragmalinguistic point of view, and its role in ensuring the artistry of the work is studied on the example of Abdulla Qahhor's stories.